Fast Solvent-free Alkylation of Amides and Lactams under Microwave Irradiation - Dariusz Bogdal (Molecules, 1999)
N-Substituted amides and lactams are rapidly N-alkylated under solvent-free phase-transfer catalytic conditions using microwaves.